The Effect of Active Assistive Range of Motion to Blood Pressure Decrease of Type II Diabetes Mellitus Patient - Handayani, Sri; Nurtanti, Susana (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
The application of physical exercise that meets Frequency, Intensities, Time, Type can be applied to control the increase in blood sugar levels and reduce blood pressure. This research is a quantitative study with a pre-experiment design using a one group pretest-posttest model. The purpose of this research is to determine the effectiveness of providing Active Assistive Range of Motion actions in the form of isotonic movements where contractions of the muscles shorten with the movements of each joint in accordance with the range of motion which is normal but the tension in the muscles remains constant during the contraction to decrease blood pressure in people with type II diabetes mellitus. This research was carried out in 2019. The population of this study were people with type II diabetes mellitus who participated in chronic disease management program activities at the Baturetno Health Center as many as 52 people. The research sample of 25 people was taken by purposive sampling technique. The results showed a decrease in systolic and diastolic blood pressure in the range of 0-15 mmHg with an average decrease of 8.6 mmHg for systolic blood pressure and 6.64 mmHg for diastolic blood pressure. Statistical test with Wilcoxon obtained Asymp value. Sig. (2-tailed) of 0,000 with a confidence level of 95% so that it can be concluded that there is a significant difference between the blood pressure of patients with type II DM before and after the Active Assistive Range of Motion treatment at Baturetno Health Center.